Chukchi reindeer herding culture - Nuvano, Vladislav (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2007)
AbstractThis research note describes a project about the relationship between humans and wild reindeer in Chukotka. The study attempts to answer the following questions: 1) How have reindeer herders managed the wild reindeer issue in the past and in the present? and 2) Which peoples have been involved in wild reindeer hunting?